2002
DOI: 10.1016/s1074-7613(02)00283-2
|View full text |Cite
|
Sign up to set email alerts
|

TL1A Is a TNF-like Ligand for DR3 and TR6/DcR3 and Functions as a T Cell Costimulator

Abstract: DR3 is a death domain-containing receptor that is upregulated during T cell activation and whose overexpression induces apoptosis and NF-kappaB activation in cell lines. Here we show that an endothelial cell-derived TNF-like factor, TL1A, is a ligand for DR3 and decoy receptor TR6/DcR3 and that its expression is inducible by TNF and IL-1alpha. TL1A induces NF-kappaB activation and apoptosis in DR3-expressing cell lines, while TR6-Fc protein antagonizes these signaling events. Interestingly, in T cells, TL1A ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
690
2
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(731 citation statements)
references
References 26 publications
27
690
2
12
Order By: Relevance
“…In contrast, our results indicated that the CpG island was highly methylated in RA synovial cells and in a synovial tissue lymphocyte fraction as well, which indicates that inflammatory conditions unique to rheumatoid joints could be responsible for the heightened CpG methylation in RA. Furthermore, our finding that expression of DR-3 was downregulated in RA synovial cells as compared with the noninflammatory OA synovial cells (see Figures 4C and D) may be responsible for the defect in apoptosis induction against TNF-like molecule 1A (TL1A), a physiologic ligand of DR-3, both in vitro (35) and in vivo (36). Our finding may also be related to findings of other studies shown that apoptosis is defective in vivo in rheumatoid synovium (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our results indicated that the CpG island was highly methylated in RA synovial cells and in a synovial tissue lymphocyte fraction as well, which indicates that inflammatory conditions unique to rheumatoid joints could be responsible for the heightened CpG methylation in RA. Furthermore, our finding that expression of DR-3 was downregulated in RA synovial cells as compared with the noninflammatory OA synovial cells (see Figures 4C and D) may be responsible for the defect in apoptosis induction against TNF-like molecule 1A (TL1A), a physiologic ligand of DR-3, both in vitro (35) and in vivo (36). Our finding may also be related to findings of other studies shown that apoptosis is defective in vivo in rheumatoid synovium (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Moreover, DcR3 can neutralize TL1A, which is an angiostatic factor in endothelial cells and provides T-cell co-stimulating signals. 22,31,32 Third, we recently observed novel actions of DcR3 in monocytes. These include: (i) the modulation of dendritic cells' (DCs) differentiation and maturation, skewing the immune response from Th1 to Th2, 33 (ii) the modulation of macrophage differentiation and impairment of macrophage function, 34 and (iii) the enhancement of monocyte adhesion.…”
Section: Introductionmentioning
confidence: 93%
“…15,18,19 Decoy receptor 3 (DcR3) is a member of the TNF receptor superfamily and has been shown to be the decoy receptor for Fas ligand (FasL), 20 LIGHT, 21 and TL1A. 22 DcR3 lacks a transmembrane domain and is regarded as a secreted molecule. Recently, several lines of evidence suggest a significant role for DcR3 in the immune suppression and tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ability of TL1A to induce apoptosis through the engagement of DR3 in some cell types, this ligand is a survival factor for T cells and promotes their expansion during the immune response. 15 Thus, the absence of CD95L and the considerable induction of TL1A in human NPCs during inflammation is unlikely to result in the massive T-cell apoptosis reported in the mouse. Accordingly, we observed that cytokine-primed NPCs did not show any cytotoxic activity on activated T cells (Figure 1h), indicating that the absence of CD95L expression of human NPCs dramatically reduced their cytotoxic potential towards T cells.…”
mentioning
confidence: 97%